High-Performance Packet Classification on Multi-Core Network Processing Platforms - 亓亚炬 薛一波 李军 (Tsinghua science and technology, 2011)
Packet classification is crucial to the implementation of advanced network services that require the capability to distinguish traffic in different flows, such as access control in firewalls and protocol analysis in intrusion detection systems. This paper proposes a novel packet classification algorithm optimized for multi-core network processors. The proposed algorithm, AggreCuts, has an explicit worst-case search time with modest memory usage. The data structure of AggreCuts is flexible and well-adapted to different types of multi-core platforms. The algorithm on both Intel IXP2850 32-bit and Cavium OCTEON3860 64-bit multi-core platforms was implemented to evaluate the performance of AggreCuts. The experimental results show that AggreCuts outperforms the best-known existing algorithm in terms of memory usage and classification speed.